UNBODY: A Poetry Escape Room in Augmented Reality - Fridolin Wild; Lawrence Marshall; Jay Bernard; Eric White; John Twycross (Information, 2021)
The integration of augmented reality (AR) technology into personal computing is happening fast, and augmented workplaces for professionals in areas such as Industry 4.0 or digital health can reasonably be expected to form liminal zones that push the boundary of what currently possible. The application potential in the creative industries, however, is vast and can target broad audiences, so with UNBODY, we set out to push boundaries of a different kind and depart from the graphic-centric worlds of AR to explore textual and aural dimensions of an extended reality, in which words haunt and re-create our physical selves. UNBODY is an AR installation for smart glasses that embeds poetry in the user’s surroundings. The augmented experience turns reality into a medium where holographic texts and film clips spill from dayglow billboards and totems. In this paper, we develop a blueprint for an AR escape room dedicated to the spoken and written word, with its open source code facilitating uptake by others into existing or new AR escape rooms. We outline the user-centered process of designing, building, and evaluating UNBODY. More specifically, we deployed a system usability scale (SUS) and a spatial interaction evaluation (SPINE) in order to validate its wider applicability. In this paper, we also describe the composition and concept of the experience, identifying several components (trigger posters, posters with video overlay, word dropper totem, floating object gallery, and a user trail visualization) as part of our first version before evaluation. UNBODY provides a sense of situational awareness and immersivity from inside an escape room. The recorded average mean for the SUS was 59.7, slightly under the recommended 68 average but still above ‘OK’ in the zone of low marginal acceptable. The findings for the SPINE were moderately positive, with the highest scores for output modalities and navigation support. This indicated that the proposed components and escape room concept work. Based on these results, we improved the experience, adding, among others, an interactive word composer component. We conclude that a poetry escape room is possible, outline our co-creation process, and deliver an open source technical framework as a blueprint for adding enhanced support for the spoken and written word to existing or coming AR escape room experiences. In an outlook, we discuss additional insight on timing, alignment, and the right level of personalization.